Examining the Use of Cosmetic Products and the Awareness of Healthy Life among University Students. - Olcer, Zeynep; Cal, Ayse; Unal, Nursemin; Oztas, Bediye; Oge, Gunay (Turkish Journal of Dermatology / Türk Dermatoloji Dergisi)
Aim: Cosmetics may be harmful to human health due to the substances they contain. University students commonly use these products. Health promotion and maintenance are closely associated with gaining healthy lifestyle behaviors, too. People need to be aware of the benefits of changing their lifestyles if they want to maintain their health and ward off illnesses. The health awareness of individuals can play a significant role in giving up their unhealthy behaviors and developing conscious behaviors. The aim of this study was to examine the use of cosmetic products and the awareness of healthy life among university students who commonly use cosmetics. Materials and Methods: This was a descriptive and cross-sectional study conducted with university students between May 2021 and February 2022. The population consisted of 2757 students, and the sample of the study consisted of 422 students who attended a foundation university and met the inclusion criteria. The data were collected from the students using an Information Form and the Healthy Life Awareness Scale over Google Forms. The data were analyzed in the Statistical Package for the Social Sciences (SPSS) software program using descriptive statistics and Mann-Whitney U test, a nonparametric test. Results: The students had a mean age of 20.24 ± 2.09 years; approximately 78.1% of them were females and they were commonly using cosmetics every day (62.3%), the most frequently used oral and dental care products (20.7%), and hair care products (20.2%). Half or fewer of the participants were aware of the symbols specific to cosmetic products, such as consumed within x days of opening, shelf life, protection against ultraviolet rays, and compliance with the standards. The awareness of healthy life was above the moderate level (59.0 ± 9.6) and was higher in those who were females and paid attention to the products' protection band, color/odor changes, and expiration date. It was observed that one-third of the participants shared their items with others, and one-quarter of them used items of others. Those who did not share their own cosmetics with others and did not use those of others had a higher awareness about healthy life. Conclusion: It was concluded that students who had high awareness of healthy life used cosmetic products more consciously. In order for young people to gain healthy life behaviors and to prevent the unnecessary use of cosmetic products, it is recommended to establish information platforms, particularly on the internet and social media, and to organize training programs that include their families and individuals in their immediate circle and also peer learning.